Intensive Laboratory experiences to safely retain experiential learning in the transition to online learning. Issue 22 (3rd November 2020) - Lashley, Marcus; McCleery, Robert
Abstract: Field‐based course work has been foundational to Ecology and Evolutionary Biology curricula. However, opportunities for these experiences gradually have decreased over the past few decades and are being replaced with technology in the college learning environment. The coronavirus disease 2019 pandemic facilitated a rapid transition of all field‐based courses to online only delivery, which we argue has forced us to reconsider how to deliver course content to retain field experiences in a manner that is safe during the pandemic but robust to ever changing constraints in the college classroom. Here, we propose pairing an intensive laboratory experience with an otherwise online delivery. We discuss several advantages of intensive laboratory experiences that occur in the field over a short but intensive time period over that of the traditional low‐intensity weekly laboratory structure. In particular, intensive laboratory experiences are safer during the pandemic because they allow the group to be tested and isolated, allow more flexibility for students with competing interests for their time, and also enhance student interpersonal skills while still providing strong reinforcement of the skills typically honed through experiential learning. We present case studies for how we intend to apply our proposed model to two courses that heavily rely on field‐based experiential learning to facilitate adoption. Abstract : We propose an intensive lab experience can safely retain experiential learning in the field during the pandemic and provide a number of advantages to the traditional lab model. Here we provide two examples of how we plan to apply our proposed model to field based courses.